Astronaut artists in cancer wards: five minutes with . . . Nicole Stott. (17th June 2019) - Mahase, Elisabeth
Abstract : The retired NASA astronaut talks about the Space for Art Foundation, a project that provides space themed art therapy for children in cancer wards